Influence of vibrations on the signals of automotive integrated radar sensors - Hau, Florian; Baumgärtner, Florian; Vossiek, Martin (2017 IEEE MTT-S International Conference on Microwaves for Intelligent Mobility, ICMIM 2017, 2017)
For automotive radar sensors the challenge is to find an optimal packaging. In addition to the mounting and the installation behind bumpers and radoms, non-linear movements like vibrations have influences on the radar performance. Therefore, integration into the vehicle environment becomes more and more important. This paper presents a theoretical description about the effects of vibration on an automotive Chirp-Sequence-FMCW radar. The simulation results are compared to real radar measurements and show good agreement. The observed effects are analysed in detail and dicussed on signal level for different vibration regimes.
CRIS-Team Scopus Importer:2023-03-08